Aerobic Exercise to Overcome Menstrual Pain in Adolescent Girls at Gemayasih Islamic Boarding School - Nurnisaa AS, Nurnisaa; Hadiaty Y, Siti (Corespub, 2024)
This study investigated the effectiveness of aerobic exercise in reducing menstrual pain among adolescent girls at Gemayasih Islamic Boarding School. Using a quasi-experimental design with pre-test and post-test measurements, 50 adolescent girls aged 14-17 years were divided into two groups: an intervention group performing aerobic exercise (n=28) and a control group performing jogging (n=22). Pain intensity was measured using the Numeric Rating Scale (0-10) over three menstrual cycles. Results showed that the aerobic exercise group experienced a more significant reduction in pain intensity (from 3.50 ± 0.600 to 1.20 ± 0.300) compared to the jogging group (from 3.60 ± 0.650 to 2.50 ± 0.600). Statistical analysis revealed a significant difference between the groups (p=0.000), with aerobic exercise demonstrating superior effectiveness in pain reduction. The study also found that participants commonly experienced additional symptoms, with emotional instability being the most prevalent (97% in the aerobic group, 90% in the jogging group). These findings suggest that aerobic exercise can serve as an effective non-pharmacological intervention for managing menstrual pain in adolescent girls within boarding school settings.